Glial sPLA2-IID is associated with resolution responses during neurotoxicity. - Benzi Juncos, Oriana Nicole (2024)
Resolution responses are associated with the metabolization of arachidonic acid (AA) and docosahexaenoic acid (DHA) by lipoxygenases. AA and DHA are released from phospholipids by phospholipases A2 (PLA2), to act as precursors of specialized pro-resolving lipid mediators (SPM). It is assumed that glial cells participate in both inflammation and resolution responses. The latter, mediated by SPM, counteract inflammatory responses. In this work, we used the pesticide maneb (MB), a well-described neurotoxicant, to study the role of glial cells in the resolution responses. We first characterize glial activation and related signaling pathways triggered by MB toxicity. Astrocytes and primary glial cultures displayed increased GFAP and S100β expression along with a greater nuclear translocation of the transcription factor NFκB. Also, astrocytes showed increased expression of Emp1, an A2 astrocyte marker, concomitantly with a decrease of the A1 marker, C3. In addition, microglia displayed increased expression of IBA-1 and decreased Arg-1 mRNA levels associated with a switch to an enlarged amoeboid flattened morphology. However, the cytokine profile showed increased interleukin-1β expression. To further explore the role of astrocytes and neurons in resolution, fatty acid profiling was assessed by GC-MS. Neurons presented increased DHA content while astrocytes displayed decreased AA and DHA levels. The respective secretomes exhibited an inverse profile, with increased DHA in the astrocytic secretome and decreased AA and DHA in the neuronal medium. In light of these findings, we analyzed Pla2g2d expression, a secretory PLA2 known for its anti-inflammatory role in immune cells. MB differentially affected Pla2g2d expression by promoting its upregulation in neurons and the downregulation in astrocytes. Concomitantly, the secretome of MB-exposed neurons restored Pla2g2d expression levels in astrocytes to control levels. In contrast, the secretome from astrocytes exposed to the pesticide downregulated Pla2g2d expression, indicating that when neurons received DHA exogenously, the enzyme was downregulated. In addition, the inhibition of secretory PLA2 prevented the astrocytic proliferative effect elicited by neurons. Our results argue in favor of the relevance of resolution pathways involving sPLA2-IID acting as a modulator of DHA levels in the glial response against the pesticide